The reality of developing the cognitive competencies of entrepreneurship among Palestine Technical College graduates (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed to identify the reality of developing the cognitive competencies for entrepreneurship among graduates of Palestine Technical College, to achieve the objectives of the study, the descriptive Analytical approach was used, and to detect whether there were statistically significant differences at the significance level (α ≤ 0.05) between the average estimates of the sample members for the degree of development of knowledge competencies in entrepreneurship among graduates of Palestine Technical College , attributed to variables: (Study program, student’s major, student’s gender, type of high school diploma, college branch), The sample consisted of (170) graduates who were randomly selected from the students of Palestine Technical College in its two branches “Deir Al-Balah Branch and Gaza Branch” during the academic year 2020/2021, A questionnaire consisting of (42) items was applied to them, distributed into (3) areas. The study concluded that the degree of development of knowledge competencies for entrepreneurship among graduates of Palestine Technical College was great. The results also showed that there were statistically significant differences between the average estimates of the sample members due to the student's specialization variable; For the benefit of engineering students, and the absence of statistically significant differences due to the variables (the academic program, gender of the student, type of high school certificate, college branch).
Keywords: reality; cognitive competencies; entrepreneurship; Palestine Technical College